2016
DOI: 10.1176/appi.ajp.2015.15020173
|View full text |Cite
|
Sign up to set email alerts
|

Defense Mechanisms of Pregnant Mothers Predict Attachment Security, Social-Emotional Competence, and Behavior Problems in Their Toddlers

Abstract: The study findings suggest that defensive functioning in parents preparing for and parenting toddlers influences the parent-child attachment relationship and social-emotional adjustment in the earliest years of life. Possible mechanisms for these associations may include parental attunement and mentalization, as well as specific caregiving behavior toward the child. Defensive functioning during times of increased stress (such as the prenatal to postnatal period) may be especially important for understanding pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…It seems probable that mothers who are more disorganized in the caregiving role are more likely to distort their infants’ behaviors and experiences. This possibility is supported by some existing research that has shown that trauma‐exposed mothers tend to have severely distorted representations of their children (Huth‐Bocks et al., ), and in turn, distorted representations pose a risk for caregiving problems and insecure mother–infant attachment (Levendosky, Bogat, & Huth‐Bocks, ; Porcerelli, Huth‐Bocks, Huprich, & Richardson, ).…”
Section: Discussionmentioning
confidence: 77%
“…It seems probable that mothers who are more disorganized in the caregiving role are more likely to distort their infants’ behaviors and experiences. This possibility is supported by some existing research that has shown that trauma‐exposed mothers tend to have severely distorted representations of their children (Huth‐Bocks et al., ), and in turn, distorted representations pose a risk for caregiving problems and insecure mother–infant attachment (Levendosky, Bogat, & Huth‐Bocks, ; Porcerelli, Huth‐Bocks, Huprich, & Richardson, ).…”
Section: Discussionmentioning
confidence: 77%
“…Possible mechanisms discussed included parental attunement and mentalization. (Porcerelli et al 2016) A large body of research has shown that an individual's attachment style influences a range of psychological and social factors (Ravitz et al 2010), including externalizing behavior problems (Guttmann-Steinmetz and Crowell 2006), internalizing psychiatric symptoms (Esbjorn et al 2012), and emotion regulation (Esbjorn et al 2012;Gillath et al 2005;Guttmann-Steinmetz and Crowell 2006;Moutsiana et al 2014;Roque et al 2013). Insecure maternal attachment was found to be associated with depression in ADHD children.…”
Section: Introductionmentioning
confidence: 99%
“…Mothers setting sub-optimal behavioral examples; mothers manifesting pathological defense mechanisms; children having reduced empathy to maternal distress, and genetics may be the major potential mechanisms underlying the association between maternal self-esteem and children’s future adaptive abilities (Creswell et al, 2005; Porcerelli et al, 2016; Xu et al, 2015). First, mothers with lower self-esteem are usually less likely to actively seek social support.…”
Section: Discussionmentioning
confidence: 99%
“…Mothers with lower self-esteem usually have lower ability to adaptively cope with stressors, and they therefore set a sub-optimal example for their children on how to react to conflicts and challenges in their future (Porcerelli et al, 2016). Second, the defense mechanism refers to the automatic psychological process that mediates responses to internal or external stressors (Porcerelli et al, 2016). Mothers with low self-esteem usually have pathological defense mechanisms and tend to ignore the thoughts and feelings of their children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation